METHODOLOGY OF STUDYING THE CONNECTED SPEECH OF MENTALLY DEFECTED CHILDREN - Aralova Iroda; Durdona (Academia Science Repository, 2023)
Development of connected speech of mentally retarded children is one of the main tasks of corrective speech therapy. Clarifying and enriching connected speech plays a big role in the development of logical thinking, and the richer the child’s vocabulary, the more clearly, he thinks and speaks fluently.